The Effect of Powder Metallurgy Parameters on Electrical Conductivity of Copper-Nickel-Tungsten Electrode - M. Sabri, A.; Zulafif Rahim, M.; A. Haikal Ahmad, M.; H. Azis, N.; Rasidi Ibrahim, M.; Mubarak Tajul Arifin, Ahmad; Ismail, Al Emran (International Journal of Engineering and Technology, 2019)
Powder metallurgy is a manufacturing process to produce a specific shape of product by using powder as the raw material. Using this technology powder can be mixed with different types of powder material to enhance the properties of the product as required. In addition, properties such as thermal, electrical and microstructure properties of the material can be efficiently controlled by controlling a numbers of parameters such as compressive load, particle size and sintering temperature of the process. This research discusses the effect of the pressure applied, the temperature of sintering, and the powder composition on the electrical conductivity of the Electrical Discharge Machining (EDM) electrode produced by powder metallurgy. Three different powder types of Copper (Cu), nickel (Ni) and tungsten (W) were mixed in this experiment with several ratios to produce the composite metal product. Several compressive load were tested to produce green compact electrode which are 7 tons, 8 tons and 9 tons. Three different sintering temperatures of 635ºC, 685ºC and 735ºC were also tested in sintering process of the green compacted electrode. In this experiment it was found that all investigated parameter significantly influenced the response. Through the analysis, the optimum electrical conductivity of EDM electrode was obtained by using 7 tonne, 5% W, and 735°C, for compaction load, composition, and temperature respectively. The highest electrical conductivity obtained is 16.425 µOhm cm.